The utopia of Rojava - Bart van Klink (Oñati Socio-Legal Series)
This article investigates how participatory art can contribute to legal change. As a case study, it discusses Jonas Staal’s project of New World Summit in Rojava, a (so far still) autonomous region in North and East Syria. It offers an interesting case, since it invites the law to include what it has excluded so far. To begin with, it is clarified how change is conceived within legal systems based on the rule of law. Although law resists radical change, it is involved in a constant process of adaptation to its environment. Subsequently, Staal’s project of New World Summit is discussed from a utopian perspective. Its apparent impossibility is what makes is so valuable for law and its development. By erecting a parliament for Rojava, it presents a picture of how the international order could look like when things were different. It basically is an exercise in “utopian world-making”.